Rapunzel syndrome: an uncommon tale of a long hairy tail - case report and review of literature - Manchikanti, Dinesh; Aggarwal, Manisha; Thomas, Shaji; Arsia, Ashish; Pusuluri, Rahul; Kumar, Sanjay (International Surgery Journal, 2021)
Trichobezoar is a rare clinical entity in which a ball of hair accumulates within the alimentary tract. When the tail of the trichobezoar extends into the small intestine, this condition is called Rapunzel syndrome (RS). A 14-year-old female presented with pain abdomen and vomiting for 2 weeks, and a history of trichotillomania and trichophagia, and an epigastric lump. A contrast enhanced computerized tomography (CECT) of the abdomen showed a grossly distended stomach with a heterogeneous mass containing trapped air with underlying normal mucosa suggestive of trichobezoar, with its tail extending into the proximal jejunum suggestive of RS. During laparotomy, a giant trichobezoar was seen in the stomach with its tail extending beyond the duodenum into the proximal jejunum. The entire specimen was delivered out intact. On follow up, she has no surgical complications, and was on behaviour therapy. Trichobezoars form when ingested hair strands become retained in the folds of the gastric mucosa and becomes entangled, forming a ball too large to exit the stomach. Trichotillomania and trichophagia are seen in many of these patients. Patients present with abdominal pain, vomiting, gastric outlet obstruction, and an epigastric mass. In the case of RS, complete removal without breakage and distal migration is important. RS should be considered as a differential diagnosis in a young girl with abdominal pain, vomiting, anaemia and upper abdominal lump. Early diagnosis prevents complications. Surgical removal is treatment of choice. Trichobezoar often coexists with psychiatric illness. Psychiatric evaluation, counselling and treatment are helpful in preventing recurrence.